Effect of Al2O3 interlayers on the microstructure and electrical response of ferroelectric doped HfO2 thin films - Lederer, Maximilian; Seidel, Konrad; Olivo, Ricardo; Kämpfe, Thomas; Eng, Lukas M. (Frontiers in Nanotechnology, 2022)
Novel devices based on ferroelectric hafnium oxide comply with the increasing demand for highly scalable embedded non-volatile memory devices, especially for in-memory computing applications. However, due to the polycrystalline nature of these hafnium oxide films, highly scaled devices face variability concerns. In order to enable smaller grains to circumvent the current limitations, the introduction of Al2O3 interlayers to interrupt the columnar grain growth is presented herein. Transmission Kikuchi diffraction is utilized to investigate influences of the Al2O3 layer on the microstructure of hafnium oxide. Moreover, electrical analysis indicates how the interlayer affects the wake-up phenomena as well as the electric field distribution within the stack. These results provide evidence on how to control grain size, electric behavior, and crystallization temperature by the insertion of Al2O3 interlayers.